Investigation of the bioherbicidal potential of rosemary on lettuce germination and initial development - Storgatto Lima, Vanessa; Frescura, Viviane Dal-Souto; Tedesco, Solange Bosio; da Silva, Antônio Carlos Ferreira (Disciplinarum Scientia | Naturais e Tecnológicas, 2025)
The objective of this study was to evaluate the bioherbicidal potential of rosemary extract (Salvia rosmarinus Spenn.) through a bioassay conducted on the germination and initial development of lettuce (Lactuca sativa L.). For this purpose, the experiment was conducted with five treatments: distilled water (negative control), 1.5% glyphosate (positive control), ethanol (negative control), 100% rosemary hydrolate, and 10% rosemary essential oil. Each treatment was performed with four replicates in a completely randomized design, where each replicate consisted of 50 lettuce seeds on germination paper in Petri dishes containing 3.4 mL of the respective treatment. The Petri dishes were placed in a B.O.D. germination chamber regulated at a constant temperature of 20 °C and a photoperiod of 12 hours for seven days. During this period, daily counts of germinated seeds were performed, and at the end, the radicle and aerial part of the lettuce seedlings were measured. This yielded the germination percentage (%G), germination speed index (GSI), radicle length (CR), and aerial part length (CPA). The data were submitted to Analysis of Variance (ANOVA) and the Scott-Knott test of means (p<0.05). The results indicated that rosemary extracts caused a significant reduction in germination and initial development of lettuce. The hydrolate at a concentration of 100% showed inhibition in all variables analyzed, indicating bioherbicidal potential.